Nurses' professional values scale‒three: Validation and psychometric appraisal among Saudi undergraduate student nurses - Abdulaziz M. Alsufyani, PhD; Ahmad E. Aboshaiqah, PhD; Fawzeih A. Alshehri, MSN; Yasir M. Alsufyani, BSN (Journal of Taibah University Medical Sciences, 2022)
الملخص: أهداف البحث: نظرا لأن القيم المهنية في التمريض قد حظيت بالاهتمام كمعيار رئيسي لرعاية تمريضية ذات جودة عالية، فقد تم قياسها باستخدام مقياس القيم المهنية التمريضية-3. ونظراً لعد توفر هذا المقياس باللغة العربية فنهدف إلى التحقق من صحة المؤشرات السيكومترية للنسخة العربية من مقياس القيم المهنية التمريضية-3 لاستخدامه بين الممرضين والممرضات السعوديين. طرق البحث: جندت هذه الدراسة المنهجية طلاب وطالبات التمريض من كليتين رئيسيتين للتمريض في المملكة العربية السعودية. تم رجوع 438 استبانة صالحة للتحليل من أصل 500 استبانة موزعة (معدل الاستجابة: 87.6%). تم ترجمة الاستبانة إلى اللغة العربية. تم التحقق من الصدق الظاهري وصدق المحتوى والصدق العاملي وصدق المفهوم باستخدام تحليلات العوامل الاستكشافية والتأكيدية. كما تم تقييم الصدق التقاربي والتمييزي. تم تقييم ثبات المقياس باستخدام معامل ألفا كرونباخ ومعامل أوميغا. النتائج: تم التحقق من الصدق الظاهري حيث تراوح مؤشر صدق المحتوى من إلى 1، بينما كان للمقياس العام. أسفر تحليل العامل الاستكشافي عن مقياس يحتوي على 28 عنصرًا بنموذج ثلاثي العوامل، موضحًا 74.5٪ من إجمالي التباين. كما أكد تحليل العامل التأكيدي أن النموذج ثلاثي العوامل كان له نتائج مقبولة. تم التحقق من ثبات المقياس عن طريق معامل ألفا كرونباخ، حيث كانت نتائجه كالتالي: 0.89، 0.90، و0.90 لكلٍ من عوامل النشاط، الرعاية، والمهنية، وكان معامل ألفا كرونباخ للمقياس العام 0.96 الإستنتاجات: تم الكشف عن مستويات كافية من الصدق والثبات للنسخة العربية من مقياس القيم المهنية التمريضية-3، مما يشير إلى ملاءمة استخدام هذا المقياس لتقييم القيم المهنية بين الممرضين والممرضات السعوديين وغيرهم من الطلاب وطالبات التمريض الناطقين باللغة العربية. Abstract: Objectives: Since the nursing professional values have garnered attention as a principal criterion for safe‒quality nursing practice, it was measured using the Nurses Professional Values Scale‒three. We aimed to validate and ascertain the psychometric indicators of the Arabic version of the Nurses Professional Values Scale–three among Saudi student nurses. Method: This methodological study recruited student nurses using convenience sampling from two nursing colleges at KSA. About 438 valid questionnaires were returned out of 500 questionnaires which were distributed over students in a formal day class time; representing a response rate of 87.6%. A 2‒fold cross‒validation process was adopted. A transcultural process was conducted. Face, content, and construct validity using exploratory and confirmatory factor analyses were used. Convergent and discriminant validity were also assessed. The reliability of the scale was assessed using Cronbach's alpha. Results: Face validity was achieved. The content validity of items ranged from .83 to 1.00, while it was .96 for the overall scale. The exploratory factor analysis yielded a scale containing 28 items with a three‒factor model, explaining 74.5% of the total variance. Confirmatory factor analysis confirmed that three‒factor solution had an adequate model fit (CMIN/df = 1.98; RMSEA = .065; SRMR = .039, CFI = .972, and GFI = .968). Convergent validity and discriminant validity were achieved. Cronbach's alpha values were .89, .90, .90, and .96 for activism, caring, professionalism, and the overall scale, respectively. Conclusion: Adequate levels of reliability and validity of the Arabic version of the Nurses Professional Values Scale–three were established, indicating the appropriateness of using this version to assess the professional values among Saudi and other Arabic‒speaking nurses.